2018
DOI: 10.1108/ijilt-09-2017-0091
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing student engagement through simulation in programming sessions

Abstract: Purpose The purpose of this paper is to explore the use of a simulator for teaching programming to foster student engagement and meaningful learning. Design/methodology/approach An exploratory mixed-method research approach was adopted in a classroom-based environment at a UK university. A rich account of student engagement dimensions (behavioural, affective/emotional, and cognitive) was captured through descriptive and inferential statistical analysis. This was triangulated through reflective and in-depth v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The findings of our previous research (Isiaq & Jamil, 2018) indicated a strong relationship between behavioural, cognitive and emotional dimensions of student engagement in simulation-based programming sessions. We found simulation capable of facilitating personalised learning, engagement and links between learning content and students' future work and profession.…”
Section: The Starting Pointmentioning
confidence: 77%
“…The findings of our previous research (Isiaq & Jamil, 2018) indicated a strong relationship between behavioural, cognitive and emotional dimensions of student engagement in simulation-based programming sessions. We found simulation capable of facilitating personalised learning, engagement and links between learning content and students' future work and profession.…”
Section: The Starting Pointmentioning
confidence: 77%
“…The following hypothesis is proposed: H5: Pleasantness of the Experience is positively associated with Memory Student engagement is the main outcome proposed in the current study. The pleasure of being in a VR environment may develop in students a motivation to be more cognitively, emotionally and behaviourally open to learn (Criado & Such, 2011;Isiaq & Jamil, 2017). We suggest that: H6: Pleasantness of the Experience is positively associated with Student Engagement As emotions contribute to generating memories and may develop the motivation to be engaged, memories of positive events are vehicles that lead students to repeat the experiences and keep them motivated and open to learning more (Itani et al 2019;Loureiro 2014).…”
Section: Literature Reviewmentioning
confidence: 94%
“…Both teachers and researchers use the concept of engagement as a predictor for learning (e.g. Abrahamsson et al, 2019;Isiaq & Jamil, 2018). However, there are still some discrepancies in how engagement is identified and defined.…”
Section: Theoretical Frameworkmentioning
confidence: 99%